U21, a novel small nucleolar RNA with a 13 nt. complementarity to 28S rRNA, is encoded in an intron of ribosomal protein L5 gene in chicken and mammals. - Qu, L H (1994)
Following a search of sequence data bases for intronic sequences exhibiting structural features typical of snoRNAs, we have positively identified by Northern assays and sequence analysis another intron-encoded snoRNA, termed U21. U21 RNA is a 93 nt. long, metabolically stable RNA, present at about 10(4) molecules per HeLa cell. It is encoded in intron 5 of the ribosomal protein L5 gene, both in chicken and in the two mammals studied so far, human and mouse. U21 RNA is devoid of a 5'-trimethyl-cap and is likely to result from processing of intronic RNA. The nucleolar localization of U21 has been established by fluorescence microscopy after in situ hybridization with digoxigenin-labeled oligonucleotide probes. Like most other snoRNAs U21 contains the box C and box D motifs and is precipitated by anti-fibrillarin antibodies. By the presence of a typical 5'-3' terminal stem, U21 appears more particularly related to U14, U15, U16 and U20 intron-encoded snoRNAs. Remarkably, U21 contains a long stretch (13 nt.) of complementarity to a highly conserved sequence in 28S rRNA. Sequence comparisons between chicken and mammals, together with Northern hybridizations with antisense oligonucleotides on cellular RNAs from more distant vertebrates, point to the preferential preservation of this segment of U21 sequence during evolution. Accordingly, this complementarity, which overlaps the complementarity of 28S rRNA to another snoRNA, U18, could reflect an important role of U21 snoRNA in the biogenesis of large ribosomal subunit.